UPAYA ORANG TUA DALAM MENANGGULANGI PERILAKU MENGKONSUMSI MINUMAN KERAS PADA REMAJA USIA SEKOLAH DI DESA SUNGAI BATANG - Edo Adrian (Tanjungpura University, 2018)
The purpose of this study is to determine the efforts of parents through prevenif social and refresive control in tackling alcohol consumption behavior in school age adolescents in the Village River Batang. This research uses descriptive method with qualitative research bench. The source of this research data is school age children and parents of school aged children who consume liquor. The data collection tool in this study uses observation guides, interview guides, and documentation studies. The results of this research are (1) Parent effort done through preventive social control has been done, this is proved on the aspect of religious value planting, parents invite and send the children to do religious worship. In the guiding aspect, parents call their son to go home late and the parents advise their children not to come home late, and on the prohibition aspect, parents forbid their children to go out for the night. (2) Parental efforts made through refresive social control have been done as evidenced through the aspect of the reprimand members, the parents of the reprimand and warning the child to leave early and on the punishment aspect, the parent gives punishment to the child consuming the liquor both the punishment psychological as well as physical punishment such as a slap.